Relationship of seasonal variations in drip water [delta].sup.13C.sub.DIC, [delta].sup.18O, and trace elements with surface and physical cave conditions of La Vallina cave, NW Spain - Kost, Oliver; González-Lemos, Saúl; Rodríguez-Rodríguez, Laura; Sliwinski, Jakub; Endres, Laura; Haghipour, Negar; Stoll, Heather (Hydrology and earth system sciences, 2023)
Cave-monitoring studies clarify the climatic, surface vegetation, and karst processes affecting the cave system and lay the foundation for interpreting geochemical stalagmite records. Here we report the monitoring of cave air, bedrock chemistry, and drip water [delta].sup.13 C.sub.DIC, [delta].sup.18 O, and [delta]D, as well as 16 trace elements, covering a full annual cycle spanning the 16 months between November 2019 and March 2021 in La Vallina cave in the northwestern Iberian Peninsula. While decreased rainfall and increased evapotranspiration in the summer months lead to a strong reduction in drip rates, there is little seasonal variation in [delta].sup.18 O and [delta]D in a given drip, likely reflecting the discrete moderately mixed to well-mixed karst water reservoirs. Small differences in [delta].sup.18 O and [delta]D between drip sites are attributed to variable evaporation intensity and/or transit times. The carbon isotope signature of the dissolved inorganic carbon of drip water ([delta].sup.13 C.sub.DIC) is likely driven by seasonal changes in the temperature controlling biological processes (vegetation and microbial soil activity), resulting in minimum [delta].sup.13 C.sub.DIC in summer and autumn months. Increased bedrock dissolution due to higher soil pCO.sub.2 in summer and autumn results in increased trace element concentrations of congruently dissolved elements. Cave air measurements (pCO.sub.2, [delta].sup.13 C.sub.air, and temperature) indicate the seasonal ventilation (winter) and stagnation (summer) of cave air. The opposite effects of reduced cave air pCO.sub.2, seasonally variable biological activity, and increased drip rate limit the extent of the seasonal variation in degassing and prior calcite precipitation (PCP) supported by trace elements (Sr/Ca index). Estimated stalagmite growth rates using monitoring data suggest biannual phases of potential calcite precipitation in summer and winter and growth cessation during spring and autumn, depending on cave and drip water conditions and the location within the cave, which has important implications for the proxy interpretation of stalagmite records.